Tax policy in the system of post COVID-19 anti-crisis measures - Shavshukov Viacheslav; Zhuravleva Natalia (SHS Web of Conferences, 2021)
Research Background: Tax policy and reforms are the means to overcome the COVID-19 crisis, contributing to economic growth. The study is based on an analysis of tax regimes before the pandemic. Purpose of the article: Purpose of the article is to develop instruments of tax regulation in anti-crisis tax policy. Methods: The analysis employs macroeconomic indicators from the IMF, and WB databases. The comparative analysis of countries in terms of Total Tax and Contribution Rate (TTCR), Labour Tax TTCR, other taxes TTCR has been conducted on the basis of WB/PWC tax ranking methodology. The paper presents a classification of tax systems according to six rankings, and suggests tax policy modifications. Findings & Value added: The main directions of tax policy reform are: 1) The tax system should maintain its progressive character while increasing social equity, a new quality of economic growth and life. 2) Income taxation is less conducive to economic growth than consumption taxation. The study suggests differentiation in tax policies for developed and developing countries. 3) The choice between a flat and a progressive personal income tax scale should be made on the bases of the thorough analysis of the tax systems of countries leading in the quality of life. Their regimes can serve as a benchmark. 4) The taxation of interest, dividends and capital gains under dual treatment is a promising tax policy direction. 5) Reforming the CIT on the basis of differentiated rental income would allow for part of the income to costs and part to profits.